Mid-infrared multi-wavelength imaging of Ophiuchus IRS 48 transitional disk. (5th April 2018) - Honda, Mitsuhiko; Okada, Kazushi; Miyata, Takashi; Mulders, Gijs D; Swearingen, Jeremy R; Kamizuka, Takashi; Ohsawa, Ryou; Fujiyoshi, Takuya; Fujiwara, Hideaki; Uchiyama, Mizuho; Yamashita, Takuya; Onaka, Takashi
Abstract: Transitional disks around the Herbig Ae/Be stars are fascinating targets in the contexts of disk evolution and planet formation. Oph IRS 48 is one of such Herbig Ae stars, which shows an inner dust cavity and azimuthally lopsided large dust distribution. We present new images of Oph IRS 48 at eight mid-infrared (MIR) wavelengths from 8.59 to 24.6 μm taken with COMICS mounted on the 8.2 m Subaru Telescope. The N -band (7 to 13 μm) images show that the flux distribution is centrally peaked with a slight spatial extent, while the Q -band (17 to 25 μm) images show asymmetric double peaks (east and west). Using 18.8- and 24.6 μm images, we derived the dust temperature at both east and west peaks to be 135 ± 22 K. Thus, the asymmetry may not be attributed to a difference in the temperature. Comparing our results with previous modeling works, we conclude that the inner disk is aligned to the outer disk. A shadow cast by the optically thick inner disk has a great influence on the morphology of MIR thermal emission from the outer disk.